IMPACT OF CORPORATE GOVERNANCE ON INTERNET FINANCIAL REPORTING IN A GROWING ECONOMY: THE CASE OF NIGERIA - ASOGWA, Ikenna Elias (Archives of Business Research, 2017)
The study aims at examining the impact of corporate governance on IFR among listed banks in Nigeria. The review of literatures reveal that IFR is one of the most efficient means of communication with investors and the practices of corporate governance by firms also influence their level of disclosures made through the internet. A quantitative research was carried out where the relationship between corporate governance variables and IFR was empirically examined. The corporate governance variables used for analyzing the impact of corporate governance on IFR include shareholders’ voting right, percentage of management ownership, percentage of block ownership and percentage of independent directors. The data on the top ten listed banks in Nigeria was collected from secondary sources from year 2010 to 2015. The findings suggest that the measures of corporate governance have significant influence on the level of IFR of banks in Nigeria, it also shows that shareholders’ voting right, percentage of independent directors and banks size have significant positive impact on the IFR of banks. The result of the regression analysis show that a negative relationship exists between managerial ownership and block ownership with IFR of Nigerian Banks. It is recommended that listed Nigerian banks should make frequent disclosures of financial information on their websites if they have high shareholder equity as source of fund in capital structure and also to attract investors and show transparency.